Direct screening of plasma circulating microRNAs - Songia, Paola (RNA Biol, 2018)
Circulating microRNAs (miRNAs) are considered as reliable candidates for biomarker discovery. RNA-Sequencing has become the most suitable technique to accurately quantify the miRNAome. However, RNA-Sequencing relies on several technical passages before reaching the final-end. HTG EdgeSeq technology, thanks to the abrogation of RNA extraction step, allows productivity enhancement by reducing the number of hands-on steps, the time for sample preparation and, therefore, the costs. We found a strong correlation between qPCR and dPCR with HTG (Pearson’s coefficient of 0.93 and 0.94, respectively). In conclusion, we showed that HTG EdgeSeq, performed on human plasma specimens without RNA extraction, is reliable, allows the simultaneous screening of more than 2,000 miRNAs, and thus, it could be applied to biomarker discovery in large cohorts.